PENEGAKAN HUKUM PERIKANAN TERHADAP ILEGAL FISHING DI INDONESIA - Sirait, Deviana Dewi; Prayoga, Nanda; Harahap, Himmatul Ummi; Diana, Sri; Siregar, Emiel Salim (Yustitia, 2024)
his journal is based on the background that Indonesia is a country that has a large area in the waters, so that foreign fishermen always escape in illegal fishing activities. The occurrence of this theft is due to the absence of attention from water inspectors. Until now, theft of this fish is still frequent. Because of this, Indonesia has to experience huge losses every year. These problems result in many parties being harmed due to the act of Illegal Fishing, so it is very necessary to enforce the law that regulates these actions.the method used to collect data is a literature study, by collecting relevant data from books, dictionaries, journals, and so on without having to conduct a field review. Based on research that has been carried out based on a review of existing literature, from the results of research data said that the Indonesian state as a coastal state that has sovereign rights to manage and utilize fish in the EEZ, for the criminal act of illegal fishing, Indonesia is considered to have criminal jurisdiction.